Risk Assessments and Safe Machinery Ensuring Compliance with the EU Directives - Jespen, Torben (Springer Series in Reliability Engineering, 2016)
This book describes the prerequisites for the placing on the market and the safe use of machinery in compliance with the relevant EU Directives, especially the Machinery Directive 2006/42. It provides readers with high-level knowledge concerning the Essential Health and Safety Requirements (EHSR) that machinery must fulfill. The approach and principles of the Machinery Directive were most recently made worldwide acknowledged in the ILO code of practice on safe machinery, released in 2013. The book addresses that code, as well as providing valuable insight into other EU Product and Workplace legislation. Focusing on the key aspect of safe machinery, the "machinery safety risk assessment", which allows readers to better understand the more difficult aspects of risk assessments, the book equips readers to tackle problems at the manufacturing stage and in different use scenarios, introducing them to risk reduction techniques and functional safety aspects.